Wall construction / Mohd Ajwad Zuhair Elah - Zuhair Elah, Mohd Ajwad (2016)
GIATMARA is an institution level training institution established under the companies act and known as GIATMARA Sedirian Berhad. Administration GIATMARA placed under MARA, an agency under the Kementerian Kemajuan Luar Bandar dan Wilayah (KKLW). The establishment of the GIATMARA in oder to provide technical skills training and vocational for youth-youth in rural areas and in the city to enable the youth get skills in preparation to be skilled manpower and technical entrepreneurs the local district and in the country. Managing budget operation GIATMARA fully funded by the goverment Malaysia through provisions that channelled through MARA. GIATMARA commenced operation in January, 1986 at GIATMARA Jitra(now known as GIATMARA Prima Kubang Pasu) with the first intake of 60 trainees in the field of Domestic ElectricityBrick laying Wood Joinery and Bend steel and high demand for the program GIATMARA cause GIATMARA fast growing in the number and programs offered. At this time GIATMARA offer 39 different types of course under 12 cluster type i.e. Mechanical, Architecture, Transporation, Manufacturing, Printing, Electric, Competer & IT, Fabric, electronic/Mechatronic, Culinary, Cosmetology & Hairdressing and hospitality. At the end of RMK 10, the number of GIATMARA expected increase 231 units throughout the country.